Research on Slow Design Concept Empowering the Cultural Tourism Integration of Rural Waterfront Landscape Spaces: A Case Study of Fairy Lake Qixi Cultural Tourist Resort in Jiangxi - Hu, Haoyu (Journal of Research in Science and Engineering, 2026)
Against the dual backdrop of global tourism transitioning toward high-quality sustainability and China’s deepening rural revitalization strategy, rural waterfront landscape spaces serve as quintessential venues for cultural-tourism integration. Their integrated development holds critical significance for rural revitalization. However, current rural waterfront cultural-tourism development commonly faces prominent issues such as excessive ecological intervention, cultural homogenization, and industrial monoculture. This study centers on the Slow Design philosophy, integrating theories such as anti-planning and living cultural transmission. Using the Fairy Lake Qixi Cultural Tourist Resort in Jiangxi as an empirical case, it employs literature review and field research to systematically explore the coupling relationship and adaptability between Slow Design and rural waterfront landscape spaces. A four-dimensional transformation strategy system—“ecological restoration—cultural revitalization—industrial integration—community participation”—is constructed. The study demonstrates that slow design—through low-intervention ecological restoration, dynamic preservation of local culture, diversified industrial synergy, and naturalized community participation—effectively addresses core challenges in Fairy Lake Qixi Cultural Tourist Resort, including ecological degradation, superficial cultural expression, and fragmented industries. This approach achieves multiple objectives: enhancing ecological resilience, transforming cultural value, optimizing industrial efficiency, and ensuring shared benefits for villagers. This research enriches the application framework of slow design in rural waterfront landscapes while providing a referenceable practical pathway for similar waterfront cultural tourism projects in southern China’s water network regions.